Abnormal changes in voltage-gated sodium channels subtypes NaV1.1, NaV1.2, NaV1.3, NaV1.6 and CaM/CaMKII pathway in low-grade astrocytoma. (1st May 2018) - Guan, Gefei; Zhao, Mingyi; Xu, Xiaoxue; Boczek, Tomasz; Mao, Xiaoyuan; Li, Zhi; Gao, Qinghua; Li, Jianing; Zhao, Dongyi; Niu, Wanting; Lei, Liming; Guo, Feng
Highlights: The expressions of NaV 1.3 and NaV 1.6 were increased in low-grade astrocytoma. The expression of CaM was increased in low-grade astrocytoma. The level of p-CaMKII/CaMKII was decreased in low-grade astrocytoma. NaV 1.3 and CaM co-localizations were increased in low-grade astrocytoma. NaV 1.6 and CaM co-localizations were increased in low-grade astrocytoma. Abstract: Epileptic seizures are the main clinical manifestation of low-grade astrocytoma. Voltage-gated sodium channels (VGSCs) play a crucial role in epilepsy. Until now, the role of VGSCs and the relationships between calmodulin (CaM)/CaM-dependent protein kinase II (CaMKII) and VGSCs in low-grade astrocytoma have not been demonstrated. In our study, the protein expression of NaV 1.3, NaV 1.6 and CaM was significantly increased in the tumor compared to control tissue, while the level of p-CaMKII/CaMKII was significantly decreased in the tumor group as determined by Western Blotting and immunohistochemistry. Furthermore, double-labeling immunofluorescence results showed that NaV 1.3/NaV 1.6 and CaM co-localization was significantly increased in the tumor group compared to control tissue. This study represents the first evidence of the abnormal changes in VGSCs subtypes and CaM/CaMKII pathway in human brain low-grade astrocytoma, providing new potential targets for molecular therapies of this disease.